Azzuri Communication Centre / Mohd Fairuz Abu Kaslan ... [et al.] - Abu Kaslan, Mohd Fairuz; Ramli, Ahmad Hafiz; Hamzah, Mohd Izwan; Suraji, Norlia Sofa; Abdullah, Siti Mariam (Faculty of Civil Engineering, 2004)
Communication is an important thing for people to connect the people around the world. One of the communication tolls is hand phone that are often used as a medium for people around the world to communicate with each other. Professional workers, middle class workers, teenagers used it to communicate with each other. Since there is few of bumiputra's involve in the business and still far behind, we are trying to explore this new field of business and try to open wide scope of this business in Malaysia. We decided to name our business as a AZZURI COMMUNICATION CENTRE, suitable with the product that we sell that is hand phone and its equipment.